Jazz revival from ancient the nation of china: yellow music to jazz - WANG LU, WANG LU; DR. ZULKARNAIN A. HATTA, DR. ZULKARNAIN A. HATTA (International Journal of Multidisciplinary Research and Studies, 2024)
To a greater extent, the "The U.S. government is encouraging jazz in China as a means of cultural exchange and rapprochement. Educators and financial resources have been sent to a country to foster the development of jazz there. In June of 2015, Blue Note Entertainment Group President Steven Bensusan announced plans to open a Blue Note jazz club at No. 23 East Qianmen Street in Beijing, the site of the previous American Embassy from 1900 to the end of the 1930s. Jazz was chosen as a means of communication between China and the United States "States. If the Chinese "As mankind emerged from the stone age into the color era, they were thrown into a whirlwind of ideas. This fervor didn't start to mellow until civilian life resumed its usual pace, at which point the natural desire to seek out pleasure, beauty, wealth, and comfort took over. This cultural and economic revival gave the intellectuals renewed faith, and many of them launched new careers. A long-standing debate about China's modernization, pitting Westernization against orientalization, was rekindled in the pivotal year of 1978. Even though it was first raised in the 1860s, at the outset of China's modernization, no satisfactory answer has ever been discovered. 4 The postmodern movement in the arts and popular culture showed signs of development "during the 1980s, suggesting a potential for future modernization in China.